2020
DOI: 10.1002/pon.5446
|View full text |Cite
|
Sign up to set email alerts
|

Advanced cancer patient preferences for receiving molecular profiling results

Abstract: Objective: This study aimed to discern preferences for receiving somatic molecular profiling (MP) results in cancer patients who have given consent to undergo testing. Methods: We conducted a mixed-methods study to explore patients' views on which MP results they would like to receive and why. Advanced cancer patients (n = 1299) completed questionnaires after giving consent to participate in a parent genomics study and undergoing MP. A subset of patients (n = 20) participated in qualitative interviews. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(32 reference statements)
0
7
1
Order By: Relevance
“…On the other hand, our sample was comparable to the general population in terms of the percentage speaking a language other than English at home (22% compared to 26% in the general population) and in terms of the percentage who had biological children (77% compared to 76% in the general population) (Australian Bureau of Statistics, 2017), indicating good generalizability in terms of these characteristics. Third, some patients were self-referred (Best et al, 2020), perhaps reflecting higher health literacy. Finally, since participants in MoST do not receive a VUS result as a result of their CTGP, this was a hypothetical question for these participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, our sample was comparable to the general population in terms of the percentage speaking a language other than English at home (22% compared to 26% in the general population) and in terms of the percentage who had biological children (77% compared to 76% in the general population) (Australian Bureau of Statistics, 2017), indicating good generalizability in terms of these characteristics. Third, some patients were self-referred (Best et al, 2020), perhaps reflecting higher health literacy. Finally, since participants in MoST do not receive a VUS result as a result of their CTGP, this was a hypothetical question for these participants.…”
Section: Discussionmentioning
confidence: 99%
“…To check which variables were associated with the desire to receive each type of result, logistic regressions were performed using SPSS Version 25. The following demographic variables, found to be significant in the previous analysis (Best et al, 2020), were included in the current analyses to control for their potentially confounding influence: age, education, language spoken at home (as a proxy for English as a second language), remote/ rural versus urban location, whether participants had biological children, and whether any first-degree relatives were diagnosed with cancer. The outcome variables relating to preferences for being informed of results were categorized as "Yes" versus "No"/"Maybe"/"Do not know" due to the small number of "No," "Maybe," and "Do not know" responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of BRCA1/2 mutation carriers and noncarriers summarized that women who were mutation carriers experienced higher emotional distress immediately after receiving results, which decreased to pretesting levels with time (Hamilton et al, 2009), highlighting the complex interplay between the impact of cancer and receipt of genetic and genomic tests on one's emotional state. In our earlier work we found that despite the possibility of genomic testing increasing psychosocial concerns particularly when receiving unwanted knowledge, the majority of advanced cancer patients were interested in receiving results, especially if they were actionable (Best et al, 2020), which is supported by other studies (Hamilton et al, 2017). Concurrently, we also found that patients had heightened optimism and hope that the result would be actionable and that a drug would be readily available and successful for their cancer, despite being informed that the likelihood of receiving an actionable result following CGP was low (Best et al, 2019).…”
mentioning
confidence: 99%